Creativity and change of context: The influence of object-context (in)congruency on cognitive flexibility. (September 2022) - van Hooijdonk, Mare; Ritter, Simone M.; Linka, Marcel; Kroesbergen, Evelyn
Highlights: The effect of object-context congruency was studied in a VR environment. Participants in the incongruent environments displayed higher cognitive flexibility. Participants in the incongruent environments also produced more original ideas. Object-incongruency did not affect fluency and the usefulness of ideas. Differences between the two incongruent environments were found. Abstract: Specific environmental features, such as natural settings or spatial design, can foster creativity. The effect of object-context congruency on creativity has not yet been investigated. While congruence between an object and its visual context provides meaning to the object, it may hamper creativity due to mental fixation effects. In the current study, virtual reality technology (VR) was employed to examine the hypothesis that people display more cognitive flexibility - a key element of creativity, representing the ability to overcome mental fixation - when thinking about an object while being in an incongruent than in a congruent environment. Participants ( N  = 184) performed an Alternative Uses Task, in which they had to name as many uses for a book as possible, while being immersed in a virtual environment that was either object-context congruent (i.e., places where you would expect a book; e.g., a library or a living room; n  = 91) or object-context incongruent (i.e., places where a book is not expected; e.g., a clothing store or a car workshop; n  = 93). The effect of object (in)congruency was also assessed for three other indices of creativity: fluency (i.e., the number of ideas generated), originality and usefulness. In line with our hypothesis, participants scored higher on pure cognitive flexibility in the object-context incongruent than in the object-context congruent environment. Moreover, participants in the object-context incongruent environment condition generated more original ideas. The theoretical and practical implications of the current findings are discussed.